Synthesis, characterization and tribological performance of two novel borate esters containing nitrogen as a multifunctional additive in synthetic ester base oil. Issue 10 (3rd August 2020) - Xiong, Sang; Zhang, Baosen; Zhang, Zhen; Wang, Qidi; Luo, Shuai
Abstract: For the development of national industry green environmental protection, the use of zinc dialkyl dithiophosphate (ZDDP) should be reduced in the process of mechanical lubrication, two novel borate esters, SS-(5-disulfanyl-1, 3, 4-thiadiazol-2-yl) O-(6-stearoyl-1, 3, 6, 2-dioxazaborocan-2-yl) carbono(dithioperoxoate) (BNSD) and 6-stearoyl-1, 3, 6, 2-dioxazaborocan-2-yl stearate (BNCD), were synthesized and characterized by FT-IR and TGA. Tribological performance of ZDDP, BNSD and BNCD as a multifunctional additive in synthetic ester base oil were investigated under different loads using a MR-S10 four-ball and MFT-3000 friction and wear test machine. A scanning electron microscope and laser scanning confocal microscope were used to observe worn scar surface morphology of the balls. The chemical compositions of worn surface were analyzed by X-ray photoelectron spectroscopy and the tribofilm of the worn surface was observed by transmission electron microscope. The TGA curves showed that BNSD and BNCD had a better thermal stability than ZDDP. BNSD exhibits excellent anti-wear and friction-reducing properties, the P B value is increase to 784 N when the optimized concentration is 0.3% the minimum WSD of BNSD-based lubricant is approximately 0.52 mm and decreased by 35% compared with the base oil. A protective tribofilm of the ball steel was analyzed by XPS and TEM, which revealed that B2 O3 and Fe2 B constitute the triboilm and about 5 nm. Therefore, BNSD could be a candidate as anti-wear and friction-reducing agent in lubricants instead of ZDDP. Graphical Abstract: uf0001